P1398The modified left atrial anterior line: optimal ablation index target to detect a transmural lesion on cardiac magnetic resonance imaging. (18th June 2020) - Ammar-Busch, S; Mahnkopf, C; Mitlacher, M; Tose Costa Paiva, B; Schwab Figueiredo, C; Butz, S; Brachmann, J; Forkmann, M
Abstract: Background: The modified anterior line (MAL) has been described as an alternative to the mitral isthmus line. Despite better ablation results, achieving a bidirectional line block is sometimes challenging. Ablation Index (AI) is a novel lesion quality marker that integrates contact force, time and power. This index has been evaluated for pulmonary vein isolation (PVI) but not for other left atrial (LA) lesions. We aimed to investigate the AI-values to determine a scar on cardiac magnetic resonance (CMR) imaging 3 months after MAL ablation. Methods: Twelve consecutive patients who underwent a MAL ablation have been included. The indication for MAL was perimitral flutter (n = 3) or substrate ablation for diffuse anterior LA low-voltage area in persistent atrial fibrillation (AF) (n = 9). The MAL was divided into three segments: segment 1 (S1) from mitral annulus to height of lower begin of left atrial appendage (LAA) antrum; segment 2 (S2) height of lower begin of LAA antrum to end of upper LAA antrum; segment 3 (S3) from end of upper LAA antrum to left superior pulmonary vein. Ablation was performed using a contact force catheter, automated lesion tagging and Ablation Index. AI target was left to the operator's choice. An inter-lesion distance of ≤ 6mm was recommended. The bidirectional block was systematically evaluated at the end of procedure. All patients underwent a CMR study at 3 months, regardless of symptoms, to identify myocardial lesions (scar). Results: Bidirectional MAL block was achieved in all patients. The mean reached AI value was 443 ± 55. CMR imaging revealed scar in 25 of 36 (69%) segments. In total, the mean AI value for detecting a scar was 451 ± 51 and was higher in S1 compared to S2 and S3 (474 ± 36 vs. 451 ± 63 vs. 423 ± 46, respectively). The AI value in S1 was significantly higher compared to S3 (p = 0.02). The minimal AI value to detect a scar was 410 ± 183 in S1, 379 ± 109 in S2 and 369 ± 68 in S3. Conclusion: Different AI targets are required for each segment of the MAL to show transmural lesions on CMR imaging 3 months post-ablation. Higher AI values are required for the lower segment of the line. Additional data are needed to demonstrate if considering these targets will be reflected in better long-term results.